KAHOOT APPLICATION FOR GRAMMAR AND READING COMPREHENSION TESTING: DESIGNING, DEVELOPING, AND VALIDATING - Dina Ayu Putri; Arifmiboy Arifmiboy (Universitas Mahaputra Muhammad Yamin, 2021)
This study aims to develop Kahoot application for grammar and reading comprehension tests on the subject of simple past tense, recount text, and narrative text. The type of this research was Research and Development (R&D) by using Borg & Gall model. There were only applied three stages in this research: 1) research and information collection 2) product planning 3) development of a preliminary form of the product. At the stage of research and information data collection, the researcher conducted need analysis. To find out the need analysis, the researcher interviewed an English teacher and some students. The next stage was product planning. In this stage, the researcher determined the exam content outline as a reference to make a quiz and collecting the material. The next stage was to develop a preliminary form of the product. It involved designing, developing, and validating the product. The subjects were 28 students in class X network computer engineering at SMKS Pembina Bangsa Bukittinggi in the academic year 2020/2021. The data collection techniques were interview and validation sheets. Based on the results of the validation sheet from three experts by the means score of percentage was obtained 68,66%, It means that English quiz using Kahoot application for grammar and reading comprehension test was feasible to be used in learning English.